Towards a Usable Framework for Modelling Security and Privacy Risks in the Smart Home - Nurse, J; Atamli, A; Martin, A (Springer Verlag, 2016)
The Internet-of-Things (IoT) ushers in a new age where the variety and amount of connected, smart devices present in the home is set to increase substantially. While these bring several advantages in terms of convenience and assisted living, security and privacy risks are also a concern. In this article, we consider this risk problem from the perspective of technology users in the smart home, and set out to provide a usable framework for modelling security and privacy risks. The novelty of this work is in its emphasis on supplying a simplified risk assessment approach, complete with typical smart home use cases, home devices, IoT threat and attack models, and potential security controls. The intention is for this framework and the supporting tool interface to be used by actual home users interested in understanding and managing the risks in their smart home environments.